Research Trends of Electric Vehicles (EVs) in Indonesia, Malaysia, and Thailand: A Quick Analysis using Bibliometric - Muji Setiyo; Indra Chandra Setiawan; Mohamad Heerwan Bin Peeie (Automotive Experiences, 2025)
The electric vehicles (EVs) market in ASEAN has seen rapid growth in 2024, driven by the global trend towards sustainable transportation and strong government support. Thailand, with strong government policies and extensive charging infrastructure, has emerged as a regional leader. Malaysia and Indonesia are still in the early stages of adoption, grappling with high vehicle costs, limited charging infrastructure, and public acceptance challenges. A bibliometric analysis of research output from 2015”“2025 reveals an exponential growth trend in EV-related studies, with Malaysian universities leading the research focus. Despite differences in progress, Indonesia, Malaysia, and Thailand face similar challenges, including limited infrastructure, high cost of ownership, and the need for greater public awareness. Tailored policies, infrastructure improvements, and regional collaboration are critical for ASEAN countries to realize their potential as key players in the global EV transition.